Market Access and Retail Investment Performance - deHaan, Ed; Glover, Andrew (The Accounting Review, 2024)
ABSTRACT We examine the effects of stock market access, and in particular trading hours, on retail investment performance. Using discontinuities around time zone borders, we find that plausibly exogenous decreases in waking trading hours are associated with meaningful increases in retail investors’ capital gains, as reported on tax returns for the U.S. population. Our results indicate that limiting trading hours curbs active retail trading, leading to improvements in portfolio performance. Our findings identify one negative effect of decreasing barriers to entry for retail investors in trading markets. JEL Classifications: M41; M48; G40; G51.